The Role of Obesity in the Development of Left Ventricular Hypertrophy Among Children and Adolescents - Brady, Tammy M. (Curr Hypertens Rep, 2016)
Both obesity and hypertension have increased substantially among children over the last several decades. At the same time, mounting evidence has pointed to the role of these and other cardiovascular disease risk factors on the development of end organ damage such as left ventricular hypertrophy in children. While traditionally thought to occur in response to an increased afterload as in systemic hypertension, evidence demonstrates that obesity is associated with left ventricular hypertrophy independent of blood pressure. Both hemodynamic and non-hemodynamic factors contribute to the pathogenesis of obesity-related left ventricular remodeling. However, more contemporary research suggests that adiposity and blood pressure have a greater effect on left ventricular geometry when present together than when present alone. Normalization of left ventricular mass in obese hypertensive individuals requires achievement of both normotension and weight loss. Additional strategies are needed to promote the cardiovascular health of children, with greater emphasis placed on obesity prevention.